'I actually know that things will get better': The many pathways to resilience of LGBTQIA+ youth in out‐of‐home care. (26th May 2021) - González‐Álvarez, Rodrigo; Brummelaar, Mijntje ten; Orwa, Samar; López López, Mónica
Abstract: Research on the lives of lesbian, gay, bisexual, transgender, queer, intersex, asexual and other forms of sexual identities and orientations (LGBTQIA+) youth in care has mainly examined their experiences from a risk‐based approach, while few studies have explored their resilience experiences. Using in‐depth interviews, the present study aims to illuminate the resilience experiences of 13 LGBTQIA+ young people in out‐of‐home care in the Netherlands. Four themes emerged from their narratives: relationships that support and empower; construction of a positive identity around their sexual orientation and gender identity and expression (SOGIE); community involvement and self‐relying strategies. Our findings support the view of resilience as a complex process that shows at an individual, interpersonal and social level.